Effects of Acute Normobaric Hypoxia on Memory Interference - Loprinzi, Paul D. (Brain Sci, 2019)
Purpose: Previous research has evaluated the effects of acute hypoxia exposure on cognitive function, notably executive function. No studies, to date, have evaluated the effects of acute hypoxia exposure on memory interference, which was the purpose of this experiment. Methods: A within-subjects, counterbalanced experimental design was employed, with condition (hypoxia vs. normoxia) and time (immediate vs. delayed) being the independent variables. Participants (N = 21; M(age) = 21.0 years) completed two laboratory visits, involving 30 min of exposure to either hypoxia (FIO(2) = 0.12) or normoxia (FIO(2) = 0.21). Following this, they completed a memory interference task (AB/AC paradigm), assessing immediate and delayed proactive and retroactive interference. Results: For retroactive interference, we observed a significant main effect for condition, F(1, 20) = 5.48, p = 0.03, ƞ(2) = 0.10, condition by time interaction, F(1, 20) = 4.96, p = 0.03, ƞ(2) = 0.01, but no main effect for time, F(1, 20) = 1.75, p = 0.20, ƞ(2) = 0.004. Conclusion: Our results demonstrate that acute hypoxia exposure was facilitative in reducing memory interference. We discuss these findings in the context of the potential therapeutic effects of acute hypoxia exposure on synaptic plasticity.